Megavoltage CT/MRI-Guided Radiotherapy with Endorectal Balloon Support for Prostate Cancer Patient with Bilateral Hip Prostheses - Hama, Yukihiro; Tate, Etsuko (Indonesian Journal of Cancer, 2024)
Introduction: Kilovoltage CT-guided radiotherapy for prostate cancer patients with bilateral hip prostheses can be challenging due to metal artifacts. Case Presentation: To compensate for reduced tissue contrast and suppress metal artifacts, a 76-year-old NCCN very high-risk prostate cancer patient underwent megavoltage CT/MRI fusion image-guided radiotherapy with an endorectal balloon. The post-treatment course was uneventful. There were no recurrences or serious side effects 11 years after radiotherapy. Conclusions: Megavoltage CT/MRI-guided radiotherapy with endorectal balloon support may be a viable alternative for a prostate cancer patient with bilateral hip prostheses.